PERAN KEPOLISIAN DAERAH KALIMANTAN BARAT DALAM PENEGAKAN HUKUM TINDAK PIDANA PENIPUAN JUAL BELI OBYEK TANAH - Manurung, Alber; Hermansyah, Hermansyah; Suhardi, Suhardi (Nestor : Tanjungpura Journal of Law, 2024)
Land issues sometimes also give rise to crimes against land, including fraudulent buying and selling of land objects, including those that occur in the jurisdiction of the West Kalimantan Regional Police.nThis research uses normative and empirical legal research at the same time. Primary data obtained through field research and secondary data obtained through library research were analyzed qualitatively to find answers to research problems. The role of the West Kalimantan Regional Police, especially through Subdit II Hardabangtah Ditreskrimum in efforts to enforce the law against criminal acts of fraudulent sale and purchase of land objects is carried out in two ways, namely: first, through a penal policy which focuses on repressive nature after a criminal act of fraudulent sale and purchase of land objects occurs and the second is through non-penal policies which are more preventive or preventative in nature. Law enforcement of the criminal act of fraudulent sale and purchase of land objects by the West Kalimantan Regional Police is influenced by factors such as the lack of quantity and quality of personnel from the West Kalimantan Police Criminal Investigation Department, the lack of community participation in uncovering criminal acts of fraudulent sale and purchase of land objects and the lack of optimal coordination with other institutions. Permasalahan tanah terkadang juga menimbulkan kejahatan terhadap tanah termasuk penipuan jual beli obyek tanah termasuk yang terjadi di wilayah hukum Kepolisian Daerah (Polda) Kalimantan Barat. Penelitian ini menggunakan bentuk penelitian hukum normatif dan empiris sekaligus. Data primer yang dudapatkan melalui penelitian lapangan serta data sekunder yang didapatkan melalui penelitian kepustakaan dianalisis secara kualitatif untuk menemukan jawaban permasalahan penelitian. Peran Polda Kalbar, khususnya melalui Subdit II Hardabangtah Ditreskrimum dalam upaya penegakan hukum terhadap tindak pidana penipuan jual beli obyek tanah dilakukan melalui dua cara, yaitu: pertama, melalui kebijakan penal yang menitikberatkan pada sifat represif setelah suatu tindak pidana penipuan jual beli obyek tanah terjadi dan yang kedua melalui kebijakan non-penal yang lebih bersifat tindakan preventif atau pencegahan. Penegakan hukum tindak pidana penipuan jual beli obyek tanah oleh Polda Kalbar dipengaruhi oleh faktor kurangnya kuantitas dan kualitas personil Ditreskrimum Polda Kalbar, kurangnya partisipasi masyarakat dalam mengungkap tindak pidana penipuan jual beli obyek tanah serta belum optimalnya koordinasi dengan lembaga lainnya.